2001
DOI: 10.1023/a:1012896916825
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of legal terminology and court proceedings in adults with developmental disabilities.

Abstract: This research compared 40 adults with mild developmental disabilities (DD) and 40 nondelayed adults (ND) in terms of knowledge of legal terms and court proceedings. For all of the 34 terms studied, with the exception of "police officer" there were significant differences between the DD and ND groups with respect to degree of conceptual understanding of terms. Results indicate that all but 6 terms assessed (adjourn, allegation, crown attorney, defendant, prosecute, and court reporter) were well-defined by 85% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Clare & Gudjonsson (1995) found that few people with IDs understood the police caution and their rights in detention in England, and Fulero & Everington (1995) have shown that this also applies to understanding of Miranda rights in the USA. Similarly, Ericson & Perlman (2001) discovered that, when asked about legal terms and court proceedings, people with IDs had a significantly less good understanding of all but one of the 34 legal terms tested than people without an ID, even though a large proportion of them had experienced direct involvement in court cases. Ericson & Perlman (2001) also found that there was a very wide range of scores, some people with IDs doing as well as some of the top scoring people without disabilities, just as was reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Clare & Gudjonsson (1995) found that few people with IDs understood the police caution and their rights in detention in England, and Fulero & Everington (1995) have shown that this also applies to understanding of Miranda rights in the USA. Similarly, Ericson & Perlman (2001) discovered that, when asked about legal terms and court proceedings, people with IDs had a significantly less good understanding of all but one of the 34 legal terms tested than people without an ID, even though a large proportion of them had experienced direct involvement in court cases. Ericson & Perlman (2001) also found that there was a very wide range of scores, some people with IDs doing as well as some of the top scoring people without disabilities, just as was reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that contacts between police and people with ID continue to be on the increase, is perhaps most problematic because of the additional disadvantage brought about by their lack of understanding of legal processes (Ericson & Perlman 2001). Indeed, the available research has consistently shown that people with ID have difficulty understanding their rights as given to them by police, that they are also likely to respond affirmatively to questions they do not understand (Gudjonsson & Clare 1992), the latter perhaps being associated to their increased risk of exploitation because of confusion about how to respond to different behavioural cues ( Wilson et al 1996).…”
Section: The Police Response To People With An Intellectual Disabilitymentioning
confidence: 99%
“…A list of authors was recorded beside the information from the codes to ascertain the most common findings. An additional subject (court language) was added as one of the papers was different in its area of research compared to the other papers included (Ericson & Perlman, 2001). The data were also analysed by the second two authors for inter-rater reliability in terms of including papers and to guard against any inclusion bias from the primary author.…”
Section: Data Synthesismentioning
confidence: 99%